Novel Retrograde Tibial Intramedullary Nailing for Distal Tibial Fractures - Min, He; Bin, Peng; Wenfu, Tan (Frontiers in Surgery, 2022)
Purpose: Postoperative distal tibial fractures are often associated with complications such as difficulties in fracture healing and surgical incision infection. The purpose of this study is to evaluate the fracture healing time and functional recovery after a retrograde tibial intramedullary nail treatment for distal tibial fractures. Methods: We retrospectively studied 9 cases of patients with distal tibial fractures treated with retrograde intramedullary nailing (IMN). Fracture healing time was based on monthly postoperative x-ray imaging results, and functional outcomes were defined according to the American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot score. Results: Among the 9 patients with distal tibial fractures from July 2020 to April 2021, the mean age was 51.5 ± 13.8 years. The classification of distal tibial fractures in the 9 patients according to OTA (Orthopaedic Trauma Association) includes 6 extra-articular fractures (3 of type A1, 2 of type A2, and 1 of type A3) and 3 intra-articular fractures (1 of type C1 and 2 of type C2).. Among them, there were 5 closed fracture cases and 4 open fracture cases (according to Gustilo classification: 2 of type I, 2 of type II). We treated the fractures surgically with new retrograde tibial intramedullary nailing. The mean follow-up time for this group was 7.9 months (5-12 months). According to monthly postoperative radiographs performed to monitor fracture healing, the mean healing time was 3.7 months (3-4 months). Final postoperative function according to the AOFAS ankle-hindfoot score shows 6 excellent cases, 3 good cases. No serious complications such as postoperative infection, bone and internal fixation exposure, osteofascial compartment syndrome, or vascular nerve injury occurred. Conclusion: The new retrograde tibial intramedullary nailing is a better method for treating distal tibial fractures with faster postoperative fracture healing, fewer complications and satisfactory functional recovery.